2001
DOI: 10.1007/s007010170137
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Chemical Shift Imaging ( 1 H CSI)-Directed Stereotactic Biopsy

Abstract: 1H CSI was feasible with the stereotactic headframe in place. The final pathological results obtained were concordant with the local metabolic information from 1H CSI. We believe that 1H CSI-directed stereotatic biopsy has the potential to significantly improve the accuracy of stereotactic biopsy targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The ratio of specific molecules correlates with a specific group of lesions or with their histological malignancy [24,25,28,29] . Single-voxel spectroscopy can differentiate gliomas according to their degree of malignancy with an accuracy of 86% and can help in the diagnosis of a high-grade glioma with an error of about 5% [32,33] .…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of specific molecules correlates with a specific group of lesions or with their histological malignancy [24,25,28,29] . Single-voxel spectroscopy can differentiate gliomas according to their degree of malignancy with an accuracy of 86% and can help in the diagnosis of a high-grade glioma with an error of about 5% [32,33] .…”
Section: Introductionmentioning
confidence: 99%
“…However, changes on MRimages are nonspecific and differential diagnosis from ischemia, encephalitis, lymphoma, subacute sclerosing panencephalitis, leukoencephalopathies and multiple sclerosis is necessary. Neither 1 1), and an increase of Cho reflecting an increased membraneturnover and increased cellularity (12,13). A recent study reported that MR spectroscopy of eight patients with GC also showed neoplastic patterns and that the histopathologic grade of GC was correlated with the extent of Cho/NAAlevel (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that high-grade gliomas revealed a 2-to 3-fold higher choline concentration compared with low-grade tumors [21] . MRS-guided stereotactic biopsy of brain tumors was shown to be feasible in several studies [22][23][24][25][26][27][28][29] . The purpose of this prospective study was to evaluate the value of CSI-guided stereotactic biopsy in the area of the highest choline concentration in suggestive low-grade gliomas.…”
Section: H-chemical-shift Imaging Of Cholinementioning
confidence: 99%